Arthroplasty - Update 2013
DOI: 10.5772/53030
|View full text |Cite
|
Sign up to set email alerts
|

Complications Following Total Hip Arthroplasty

Abstract: 2. Systemic / non-surgical 2.1. Thromboembolic complications Deep Vein Thrombosis Distal deep vein thrombosis (DVT) can range from being asymptomatic, to resulting in long term valvular damage resulting in chronic venous insufficiency. Proximal propagation can result in more serious pulmonary embolism. The overall incidence of DVT, including both radiologically diagnosed asymptomatic DVT and symptomatic DVT, post THA in early studies was reported to be as high as 70% without any form of prophylaxis [15]. Recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 221 publications
(230 reference statements)
0
2
0
Order By: Relevance
“…Also, a study discussing THA revision due to dislocation concluded that the posterior approach increased the risk of revision for dislocation by 1.7 times [6,9]. Correspondingly, a posterior approach has been shown to be a major risk factor for dislocation due to reduced cup anteversion, which may be related to surgeon expertise [13].…”
Section: Discussionmentioning
confidence: 99%
“…Also, a study discussing THA revision due to dislocation concluded that the posterior approach increased the risk of revision for dislocation by 1.7 times [6,9]. Correspondingly, a posterior approach has been shown to be a major risk factor for dislocation due to reduced cup anteversion, which may be related to surgeon expertise [13].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, THA has been performed on a large number of patients worldwide. It is among the most frequently executed orthopaedic operations, and is an increasingly common and successful operation of the last decades [2][3][4]. Today the average lifetime of a hip prosthesis is approximately 15 years [5,6].…”
Section: Introductionmentioning
confidence: 99%